Profiling Farmer Producer Companies (FPCs) in Rajasthan: Insights into their Impact and Operations - , Latika Sharma; , Narendra Yadav; , Binoo P Bonny (Archives of Current Research International, 2025)
Farmer Producer Companies (FPCs) reveal a transformative model to empower farmers by fostering collective action and ensuring fair returns for their produce. The main aim of the Farmer Producer Company is to ensure a better income for the producers through an organization of their own. Small producers do not have the volume individually to get the benefit of economies of scale. Methodology: This study examines the profiling of Farmer Producer Companies (FPCs) in Rajasthan, highlighting their significance in enhancing the well-being of smallholder farmers. The study was conducted during 2022-23 in Rajasthan with a sample of 30 FPCs. 30 FPCs were selected in proportion based on their business activities. Findings: The analysis reveals that 95 percent of FPCs in Rajasthan have been established for 5 to 10 years. A significant proportion of these organizations, 77 percent, have an annual turnover of up to 50 lakh INR, while 70 percent possess share capital ranging from 5.1 to 9.9 lakh INR. Community engagement is evident, as 46.67 percent of FPCs have between 500 to 750 shareholders. Gender diversity within these organizations is notable, with 30 percent of board members are female, suggesting a need for increased promotion of women's participation. The profile of CEOs is constitute of age, annual income, experience etc. among these constitutes nearly 70 percent CEO have on an average 7.5 year experience and are over 35 years old, with most being full-time, paid executives earning up to 4 lakh INR annually. The study also identifies garlic as the region's predominant produce procured by FPCs. These findings underscore the pivotal role of FPCs in fostering agricultural development and community involvement in Rajasthan.